PALMAR AND DIGITAL DERMATOGLYPHIC PATTERNS IN INFERTILE MALES IN THE POPULATION OF BIHAR - Bheem Prasad; Sarita Kumari; Padamjeet Panchal; Dayanidhi Kumar (Medico Research Chronicles, 2018)
Background: Dermatoglyphics is a science which can help to predict occurrence of a specific disease. Dermatoglyphics may be useful to find out suspected infertile male patients from a large population which can further be subjected to more investigations. Different diseases have different dermatoglyphic patterns associated with them. Some diseases showing association with Dermatoglyphics include Sickle cell anaemia, congenital heart disease, Rheumatoid Arthritis, Diabetes mellitus, Down’s syndrome and Cancers such as Breast and Prostate.Objective: The purpose of this study is to compare the frequencies of different fingerprint patterns of infertile males with normal populations.Materials and Methods: This study was conducted on 108 infertile male patients with abnormal semen profile and compared with an equal number of age matched fertile males. We studied fingerprint patterns in all subjects.Result: Loop was the commonest pattern followed by Whorls and Arch in both groups. There is a significant difference between the numbers of arches in infertile cases and controls. We also found the statistically significant difference between patterns of finger ridge count in thumb and ring finger (left hand) of infertile males and controls. The mean of atd angle, dat angle and adt angle on the left hand of infertile males were statistically significant from those of the controls. Whereas the mean of all these angles is not being statistically significant in right hand of both cases as well as controls.Conclusion: Dermatoglyphics may be used for infertility screening of a large population because it is simple, non-invasive and inexpensive technique. It may be also used as a supportive investigatory tool for clinicians.